Physiological analyses of swallowing changes due to chronic obstructive pulmonary disease in anesthetized male rats - Nagoya, Kouta; Tsujimura, Takanori; Yoshihara, Midori; Watanabe, Masahiro; Magara, Jin; Kawasaki, Katsushige; Inoue, Makoto (Frontiers in Physiology, 2024)
Chronic obstructive pulmonary disease (COPD) was previously known as chronic bronchitis and emphysema. It has various main symptoms, such as dyspnea, chronic cough, and sputum, and is often accompanied by dysphagia. Although many published clinical reports have described COPD-related dysphagia, the physiological mechanisms underlying swallowing changes due to COPD remain unclear. Therefore, we analyzed how COPD affects the swallowing reflex using COPD model rats.We performed an electrophysiological study of respiration and swallowing using COPD model rats induced by intratracheal administration of porcine pancreatic elastase (PPE) and lipopolysaccharide (LPS) in Sprague-Dawley male rats. To identify the respiration and swallowing responses, electromyographic (EMG) activity was recorded from the diaphragm (Dia), digastric (Dig), and thyrohyoid (TH) muscles.We confirmed COPD using micro-computed tomography (CT) analysis and hematoxylin and eosin (HE) staining of the lungs. The duty cycle was defined as the ratio of the inspiration duration to the total respiratory duration. In COPD model rats, the duty cycle was significantly higher than that in control rats. The frequency of the swallowing reflex evoked by electrical stimulation of the superior laryngeal nerve (SLN) during the inspiration phase was higher in COPD model rats than in control rats. Furthermore, long-term COPD altered Dig and TH muscle activity without pathological muscle change.Our results suggest that COPD increases the frequency of swallowing initiation during the inspiration phase. Furthermore, long-term COPD affects swallowing-related muscle activity rather than causing pathological muscle changes. These physiological changes may increase the risk of developing dysphagia. Further studies are necessary to clarify the mechanisms contributing to the functional changes in respiration and swallowing in COPD model rats.